Expression of wild-type and recombinant D4-CK domains of VWF gene with novel variants in Pakistan - Arshia Latif; Muhammad Asif Naveed; N. A. Shabana (Molecular Biology Reports, 2026)

Mutation mapping and functional characterization of a missense mutation p.Arg228Cys in ALDH3A2 gene causing Sjögran-Larson syndrome - Muhammad Zeeshan Ali; Samia Sattar; Abdulfatah M. Alayoubi; Shakil Abbas; Mohammed Turki Hussain Alharthi; Alwaleed Fahad H. Altemani; Muhammad Latif; Muzammil Ahmad Khan; Christian Windpassinger (Molecular Biology Reports, 2026)

Multiplexed CRISPR/Cas9 mediated knockdown of BCH gene in potato enhances beta-carotene to combat vitamin A deficiency - Ujala Nasir; Aneela Yasmeen; Muhammad Awais; Ayesha Latif; Allah Bakhsh; Nadeem Ahmad; Naila Shahid; Saira Azam; Abdul Qayyum Rao; Ahmad Ali Shahid (Plant Science, 2026)

Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Uncovering the central role of GhSPL13 in vegetative growth, root architecture, and stress responses in cotton - Sahar Sadaqat; Muhammad Awais; Muhammad Saad bin Tahir; Ramsha Ajmal; Aneela Yasmeen; Saira Azam; Naila Shahid; Ayesha Latif; Allah Bakhsh; Ruhangiz Mammadova; Abdul Qayyum Rao (Plant Science, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Deciphering the role of potato peel on sunflower hybrids growth, photosynthesis, osmoregulation, oxidative defense and ion uptake under salinity - Sundas Fatima; Aasma Tufail; Muhammad Bilal Hafeez; Samreen Nazeer; Noreen Zahra; Fatima Latif; Sabina Asghar; Muhammad Ahsan; Muhammad Hamza; Muhammad Zubair Akram (Biocatalysis and Agricultural Biotechnology, 2026)

Returning straw and applying appropriate nitrogen fertilizer could increase acid-hydrolysable ammonium nitrogen and amino sugar nitrogen in the soil, thereby promoting effective panicle number and ultimately boosting rice yield - Linya Lu; Zhengli Song; Yang Hu; Liang Luo; Guiling Xu; Yuehua Feng; Muhammad Usama Latif; Somsana Phonenasay; Bingping Cui; Xiangjun Xu; Jianhua Huang; Yanni Wei (Plant and Soil, 2026)

Methotrexate Loaded Polymeric Patches with Penetration Enhancers for Transdermal Delivery: in vitro, Ex Vivo, and in Vivo Characterization - Muhammad Shahid Latif; Asif Nawaz; Muhammad Khurshid Alam Shah; Muhammad Fareed; Muhammad Waseem Khan; Muhammad Luqman Nordin; Omar Awad Alsaidan; Sami I. Alzarea (Journal of Pharmaceutical Innovation, 2026)

Integrative reverse vaccinology and computational modeling for the rational design of a broadly immunogenic multi-epitope vaccine against Marburg virus infection - Asadullah Khan; Sitara Bibi; Li Pinyi; Khalida Latif; Muhammad Rahiyab; Ishaq Khan; Arshad Iqbal; Itazaz Ul Haq; Syed Shujait Ali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Structure-based immunopharmacological design of a multi-epitope vaccine candidate against Naegleria fowleri targeting TLR3: a pan-genomic and molecular dynamics approach - Rabia Faizan; Muhammad Naveed; Inmaculada Bellido Estevez; Hafiz Muzzammel Rehman; Ayesha Latif; Hafiz Muhammad Hammad; Abdul Rafay Khan; Seham O. Alsulami; Maha A. Aljumaa; Nantenaina Tombozara (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Insights into the Contortylenchus genitalicola (Tylenchida: Allantonematidae) parasitism in Monochamus alternatus (Coleoptera: Cerambycidae) in China - Lichao Wang; Huan Li; Yajing Song; Junwei Wang; Muhammad Faizan Latif; Chenning Zhang; Ming Xu; Min Li; Fengmao Chen (Journal of Invertebrate Pathology, 2026)

E-Waste-Derived Highly Sensitive and Scalable Flexible Fractal Capacitive Sensors-Based Smart Wearable Joint Orthosis System for Post-Surgical Rehabilitation - Amna Tariq; Nida Iqbal; Rimsha Sarwar; Asma Latif; Saman Iqbal; Muhammad Hamza Zulfiqar (Journal of Medical and Biological Engineering, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Valorization of recycled concrete fine aggregates in gypsum mortars for developing eco-friendly false ceiling plates - Rashid Latif; Muhammad Rizwan Riaz; Anam Fatima; Rizwan Azam; Muhammad Hassan Javed (Innovative Infrastructure Solutions, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Improving Wheat Production in Pakistan Through an Economically Viable Solar‐Powered Rain Gun Sprinkler Irrigation System - Muhammad Asif; Shahzad Hussain Dahri; Bashir Ahmad; Noman Latif Sadozai; Sohail Raza Haidree; Abdul Hannan; Syed Qasim Ali Naqvi (Irrigation and Drainage, 2026)
In rainfed agriculture, limited water availability has become a challenging factor for sustainable farming and economic security. For regions with variable climate conditions, efficient water management practices must be adopted to improve livelihoods and food security. This study aimed to evaluate the role of supplemental irrigation for wheat crops in the Pothwar region. The irrigation management consists of I 0 (rainfed), I 1 (10 mm presowing), I 2 (10 mm at 50% soil moisture depletion [SMD]) and I 3 (25 mm at 75% SMD). The results revealed that, under I 3 , the grain yield increased by 49% and 17%, followed by I 2 (47% and 12%) compared to the rainfed yield of 1.85 and 3.93 tons/ha in Jand and NARC, respectively. The analysis of variance and Tukey's honestly significant difference (HSD) test revealed that the yield for I 0 value was significantly lower than that of all the irrigation treatments, while there were no significant differences among I 1 , I 2 and I 3 . The net benefit analysis revealed that I 3 was an economic irrigation schedule and paid back the total intervention cost by generating PKR 389,915/ha at NARC and PKR 283,915/ha at Jand in 3.83 and 4.93 years, respectively. This viable economic return makes solar‐powered irrigation systems reliable sources of water for water‐scarce and climate‐variable regions.

Molecular prevalence, genetic diversity and effect of Toxoplasma gondii infection on the hematological parameters of various bird species - Tauqir Un Nisa; Fatima Mushtaq; Humaira Zulfiqar Ali Gondal; Naila Amjad; Muhammad Usman; Muhammad Ali; Muhammad Latif; Hira Muqaddas; Furhan Iqbal (Biologia, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Black carbon and its relationship with PM2.5 and NO2 in a high-traffic urban environment of Kuala Lumpur - Murnira Othman; Mohd Talib Latif; Haris Hafizal Abd. Hamid; Ethel Garcia; Muhammad Ikram A. Wahab; Santhyami Santhyami; Li Li (Urban Climate, 2026)

A highly efficient nanocopper hydroxide activates plant immune resistance and confers tolerance to salt and drought stress in rice - Chongchong Lu; Zimeng Li; Taizhong Huang; Muhammad Zunair Latif; Haifeng Liu; Mingxia Hao; Yanke Jiang; Yingzhe Yue; Jian Zhang; Miaomiao Deng; Qian Du; Sifan Yang; et al. (Chemical Engineering Journal, 2026)

El Niño-Southern Oscillation-driven variability in drought severity across the Upper Indus Basin, Pakistan - Yasir Latif; Muhammad Yaseen (Theoretical and Applied Climatology, 2026)

Study of Molecular Docking and Evolutionary Dynamics of the FGF Gene Family in Nile Tilapia - Muhammad Farhan Khan; Shakeela Parveen; Muhammad Abdul Manan; Fariha Latif; Alfabetian Harjuno Condro Haditomo; Youhou Xu; Peng Zhu; Laiba Shafique (Marine Biotechnology, 2026)

Southward to northward shifting trends of monsoonal precipitation and their connections with atmospheric circulations over Pakistan: A comparative study of 1961–1990 and 1991–2020 - Sohail Abbas; Amina Ameer; Fenglin Lv; Tingting Li; Yi Chen; Liang Cao; Heli Lu; Yasir Latif; Muhammad Yaseen; Siqi Lu; Wanfu Feng; Amjad Ali Khan (Journal of Hydrology, 2026)

Impact of Thermal Damage on the Physical and Mechanical Properties of Carbonate Rocks - Subhan Ullah; Muhammad Sajid; Khalid Latif; Abdul Rahim Asif; Muhammad Rizwan (Geotechnical and Geological Engineering, 2026)

In-silico genome-wide identification of ADF gene family in Brassica napus under long-term high-temperature stress - Enerand Mackon; Shanshan Zhang; Zhuyu Pan; Muhammad Ikram; Latif Ullah Khan; Wajid Saeed; Muhammad Waseem; Yun Li; Pingwu Liu (Genetic Resources and Crop Evolution, 2026)

Cambrian sequence stratigraphy and depositional dynamics: insights from the Xuankong Temple section, Shanxi, China - Muhammad Riaz; Ziliang Liu; Khalid Latif; Changcheng Wang (International Geology Review, 2025)

Transition of the Karakoram anomaly under emerging hydroclimatic trends - Yasir Latif; Sara C. Pryor; Sardar Ateeq-Ur-Rehman; Sher Muhammad; Muhammad Yaseen; Muhammad Atif Wazir (Science of The Total Environment, 2025)

Retraction notice to “Citric acid-capped NiWO4/Bi2S3 and rGO-doped NiWO4/Bi2S3 nanoarchitectures for photocatalytic decontamination of emerging pollutants from the aqueous environment” [Environ. Res. Volume 212, Part B, September 2022, 113276] - Hina Liaquat; Muhammad Imran; Shoomaila Latif; Sajid Iqbal; Nazim Hussain; Muhammad Bilal (Environmental Research, 2025)

Prevalence of New Delhi Metallo-β-lactamase (blaNDM) gene in a selected population of drug-resistant clinical isolates - Muhammad Shafiq; Aftab Ahmad; Kunza Latif; Muhammad Saeed; Iftikhar Ahmed; Muhammad Zeeshan Hyder (Molecular Biology Reports, 2025)

Enhancing Rice Water Productivity: Insights From Crop Water Needs and Irrigation in Pakistan - Ghani Akbar; Noman Latif Sadozai; Muhammad Ashraf (Irrigation and Drainage, 2025)
Excessive irrigation significantly reduces rice ( Oryza sativa L.) water productivity in Pakistan. This study evaluated crop water requirements, irrigation trends and water productivity across Pakistan's rice‐growing regions. Field data on crop yield, soil characteristics, irrigation practices and 10 years of weather data were collected from 11 districts across four provinces. The FAO AquaCrop model was used to assess crop water requirements (evapotranspiration, ET), the root zone water balance and water productivity. The crop water requirements ranged from 787 to 1151 mm, while irrigation consistently exceeded these needs by 95% to 123%. The irrigation water productivity (WPi) ranged from 0.09 to 0.19 kg/m 3 , and the evapotranspiration (ET) water productivity (WPet) ranged from 0.20 to 0.41 kg/m 3 . Excessive irrigation, 2 to 3 times the actual crop water needs, is attributed to traditional practices, a lack of knowledge and suboptimal irrigation schedules. Optimizing irrigation scheduling, adopting advanced technologies, and using high‐yielding, drought‐tolerant rice varieties could reduce water losses and improve crop yields. These findings offer actionable strategies to increase water productivity and ensure food security in Pakistan's rice‐growing regions, with potential applications in other water‐scarce, rice‐producing countries facing similar challenges.

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Development and characterization of Zingiber zerumbet rhizome crude extract-loaded nanoemulsions: In vitro release and cytotoxicity assessment against MDA-MB-231 breast cancer cell line - Zahra Sanaimehr; Norazlinaliza Salim; Emilia Abdulmalek; Intan Nur Fatiha Shafie; Muhammad Alif Mohammad Latif; Renny Apriliana M. Ansori; Sharida Fakurazi (South African Journal of Botany, 2025)

Submergence stress in plants: molecular mechanisms, physiological changes, and adaptive responses - Noreen Iftikhar; Muhammad Saad Bhutta; Narmeen Tariq Zaman; Ayesha Khalid; Ayesha Latif; Saira Azam; Naila Shahid; Aneela Yasmeen; Abdul Qayyum Rao (Physiology and Molecular Biology of Plants, 2025)

Effect of Halamphora coffeaeformis supplementation in rice bran biofloc on the growth and survival of black tiger shrimp (Penaeus monodon) postlarvae - Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Hazwani Hanim Hasnan; Ninie Diana Baharuddin; Kamil Latif; Clement R. de Cruz; Murni Karim; Hui Teng Tan; Yam Sim Khaw; Jeffrey K. C. Lee; Ikhsan Natrah (Aquaculture International, 2025)

Biochar and GO doped biochar powder for photocatalysis, adsorption, and latent fingermark detection - Abaid Ullah; Aliya Zahid; Shaista Ali; Aniza Latif; Muhammad Shahid; Atia Sarfraz; Muhammad Akhyar Farrukh (Journal of Water Process Engineering, 2025)

Tropical-extratropical interactions: the atmospheric dynamics behind Dubai's extreme precipitation in April 2024 - Muhammad Latif; Muhammad Usman; Abdul Malik; Sateesh Masabathini; Burhan Ahmad; Luqman Atique; Fatima Alhammadi; Ibrahim Hoteit (Natural Hazards, 2025)

Mitigating Terminal Drought in Chickpea (Cicer arietinum L.) Using Organic Manures; Effects on Yield, Potassium Uptake and Antioxidants Activity - Malik Muhammad Yousaf; Azra Yasmeen; Shadia Hama Salih Kareem; Muhammad Arif; Hesham F. Alharby; Hameed Alsamadany; Yahya M. Alzahrani; Amnah M. Alamri; Ammara Latif; Hafeez ur Rehman (International Journal of Plant Production, 2025)

Investigating the development and success of Spodoptera Frugiperda (Lepidoptera: Noctuidae) on various wheat varieties: an age-stage specific life table analysis - Hamza Latif; Muhammad Arshad; Muhammad Irfan Ullah; Gulfam Yousaf; Nahdia Perveen; Wafa Abdullah Hamad Alkherb; Mohammed Ali Alshehri; Samy M. Sayed (International Journal of Tropical Insect Science, 2025)

DusVax: a universal pan-viral multi-epitope vaccine (PV-MEV) for pandemic preparedness against ten high-priority viral pathogens - Allah Rakha Yaseen; Muhammad Suleman; Mahrukh Afzal; Hania Usama; Warda Ashfaq; Sehrish Firyal; Ayesha Arif; Amna Latif; Ali Asghar; Abdul Salam Qadri (The Nucleus, 2025)

Formulation and Characterization of Isavuconazole-Loaded Chitosan/Sodium Alginate Nanoparticles for Dermal Delivery: in Vitro and in Vivo Evaluation for Enhanced Antifungal Therapy - Shahzad Khan; Asif Nawaz; Muhammad Khursheed Alam Shah; Muhammad Shahid Latif; Muhammad Haroon; Abdullah Khan; Tarek Mohamed Ali Elsayed (Journal of Pharmaceutical Innovation, 2025)

Investigation of geoenvironmental contamination and risks of municipal solid waste disposal sites in urban Khyber Pakhtunkhwa, Pakistan - Muhammad Ayaz Khan; Abdullah Khan; Zia ur Rahman; Azhar Rashid; Khalid Latif (Environmental Geochemistry and Health, 2025)

Peatland fires in Peninsular Malaysia act as primary source of dioxins, dioxin-like polychlorinated biphenyl, and particulate matter - Ahmad Shalihin Mohd Samin; Nur Batrisyia Hadfina Azmi; Mohd Talib Latif; Yin-Hui Leong; Tengku Sifzizul Tengku Muhammad; Wen Sheng; Norhaniza Amil (Environmental Monitoring and Assessment, 2025)

Weissella confusa MW051433 Mitigates Hypercholesterolemia by Biliary Cholesterol Excretion: The In Vivo Evidence - Saman Javed; Zakia Latif; Ghulam Ayesha Javed; Aneela Munir; Maria Mushtaq; Mamoona Hameed; Muhammad Arshad; Najma Arshad (Current Microbiology, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

FLTrans-Net: Transformer-based feature learning network for wheat head detection - Samia Nawaz Yousafzai; Inzamam Mashood Nasir; Sara Tehsin; Norma Latif Fitriyani; Muhammad Syafrudin (Computers and Electronics in Agriculture, 2025)

Impact of silicon nitride nanoparticles on soil organic carbon dynamics in subtropical evergreen forest ecosystems of China: An incubation study - Fasih Ullah Haider; Ahmad Latif Virk; Shuyidan Zhou; Noor ul Ain; Luis Carlos Ramos Aguila; Kadambot H.M. Siddique; Muhammad Farooq; Yuelin Li (Science of The Total Environment, 2025)

Control of H2S synthesis by the monomer–oligomer transition of OsCBSX3 for modulating rice growth-immunity balance - Haimiao Zhang; Baolong Sun; Muhammad Zunair Latif; Yang Liu; Lei Lv; Tao Wu; Yang Li; Ziyi Yin; Chongchong Lu; Haipeng Zhao; Lingguang Kong; Xinhua Ding (Molecular Plant, 2025)

Retraction notice to “Degradation of cefadroxil drug by newly designed solar light responsive alcoholic template-based lanthanum ferrite nanoparticles” [Environ. Res. 231P3 (2023) 116241] - Ammara Nazir; Muhammad Imran; Farah Kanwal; Shoomaila Latif; Ayesha Javaid; Tak H. Kim; Grzegorz Boczkaj; Ashwag Shami; Hafiz Iqbal (Environmental Research, 2025)

Investigation of depositional fabric and its impact on the geomechanical behavior of limestones - Subhan Ullah; Muhammad Sajid; Khalid Latif; Abdul Rahim Asif; Muhammad Rizwan; Umair Mussawar; Shuja Ullah (Carbonates and Evaporites, 2025)

Photocatalysis mediated removal of diclofenac potassium and energy storage efficiency of bismuth doped cerium tungstate - Ayesha Javaid; Muhammad Imran; Farah Kanwal; Shoomaila Latif; Muhammad Naeem Khan (Journal of Water Process Engineering, 2025)

Characterization of mercury ameliorating rhizobacteria for enhancing growth and yield of Triticum aestivum L. in the field: An in-vitro and in- silico study - Aatif Amin; Muhammad Naveed; Sunbul Rasheed; Zakia Latif; Tariq Aziz; Fahad Al Asmari; Maha Aljabri (South African Journal of Botany, 2024)

Diagnostic study on extreme precipitation over Karachi during August 2020 - Amna Bibi; Shahzada Adnan; Muhammad Latif; Azmat Hayat Khan; Anjum Nazir Zaighum; Kalim Ullah (Meteorology and Atmospheric Physics, 2024)

Soil Organic Carbon and Aggregate Associated Changes in Three Subtropical Evergreen Forest Ecosystems of China - Fasih Ullah Haider; Ahmad Latif Virk; Lili Nian; Muhammad Farooq; Juxiu Liu; Mengmeng Yang; Wanxuan Huang; Yuelin Li (Journal of Soil Science and Plant Nutrition, 2024)

Experimental investigation of the wake of tandem cylinders using pivoted flapping mechanism for piezoelectric flag - Muhammad Mahad Shah; Rizwan Mahmood; Usman Latif; Emad Uddin; Adnan Munir; Ming Zhao; Hafiz Hamza Riaz (Ocean Engineering, 2024)

In-depth analysis of ambient air pollution changes due to the COVID-19 pandemic in the Asian Monsoon region - Mohd Talib Latif; Noorain Purhanudin; Nur Zulaikha Mohd Afandi; Maria Obiminda L. Cambaliza; Nor Diana Abdul Halim; Nor Syamimi Sufiera Limi Hawari; To Thi Hien; Ohnmar May Tin Hlaing; Warnakulasuriya Roshani Loreta Hiranthi Jansz; Muhammad Fahim Khokhar; Puji Lestari; Shih-Chun Candice Lung; et al. (Science of The Total Environment, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Drought variability in Pakistan: Navigating historical patterns in a changing climate with global teleconnections - Muhammad Latif; Hira Shireen; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi (Theoretical and Applied Climatology, 2024)

Geospatial identification of possible rainwater harvesting locations within a high-altitude Gilgit River basin, Pakistan - Madiha Asif; Muhammad Yaseen; Syed Umair Shahid; Yasir Latif; Salma Anwar; Sohail Abbas (Theoretical and Applied Climatology, 2024)
The management of water resources is no longer an option but a necessity especially in countries with a high rate of population growth like Pakistan. Pakistan has a high-water scarcity, an extremely varying topography, and is also one of the countries encountering the problem of climate change. Therefore, prudent utilization of available water resources is a matter in the plains of Pakistan as in its high-altitude regions. Instead of wasting water which is a valuable resource, rainwater harvesting is a way of saving rainwater as an alternative source of fresh water for better use. The aim of this study was to search for potential rainwater-harvesting areas in a high-altitude Gilgit River basin. This research employed the SCS-CN technique in estimating surface runoff in the GIS environment. The geospatial study used four input parameters: slope of the land, land covers, surface runoff and drainage density. The research concluded that some lands, especially those that are deserted in dry area and agricultural lands, can serve as the sites of rainwater harvesting, with only 4% of area that was highly suitable for the purpose. Nevertheless, 37% of the investigated area was shown as totally unviable for rainwater collection installations because of steep slopes and substantial volume of snow. Simultaneously, the rainwater storage design solutions suggested were check dam, percolation tank, and agricultural ponds with the area of 3.5%, 1%, and 0.75% of the given land area, respectively, for rainwater harvesting. The locations of potential catchment and planned rainwater harvesting structures would assist the local authorities and the policy makers to provide plans and design on the construction of water storages and also the optimization of water use.

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

Retraction Note: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2024)

Transgenic expression of artificial microRNA targeting soybean mosaic virus P1 gene confers virus resistance in plant - Muhammad Faizan Latif; Jingquan Tan; Wang Zhang; Wenxuan Yang; Tinghui Zhuang; Wenlong Lu; Yanglin Qiu; Xinying Du; Xinjian Zhuang; Tong Zhou; Jiban K. Kundu; Jinlong Yin; et al. (Transgenic Research, 2024)

The concentration of particulate matters in mechanically ventilated school classroom during haze episode in Kuala Lumpur City Centre - Azwani Alias; Mohd Shahrul Mohd Nadzir; Mohd Talib Latif; Md Firoz Khan; Haris Hafizal Abd Hamid; Mazrura Sahani; Muhammad Ikram A. Wahab; Murnira Othman; Faizal Mohamed; Noorlin Mohamad; Norhaniza Amil; Otuyo Muhsin Kolapo (Air Quality, Atmosphere & Health, 2024)

Recognition of the inducible, secretory small protein OsSSP1 by the membrane receptor OsSSR1 and the co-receptor OsBAK1 confers rice resistance to the blast fungus - Tianfeng Zhao; Shijie Ma; Ziying Kong; Haimiao Zhang; Yi Wang; Junzhe Wang; Jiazong Liu; Wanzhen Feng; Tong Liu; Chunyan Liu; Suochen Liang; Shilin Lu; et al. (Molecular Plant, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Molybdenum oxide-based catalyst towards better hydrogen production: effects of isothermal carburization - Mohd Nor Latif; Nur Syakirah Abdul Rahim; Salma Samidin; Siti Hasnawati Jamal; Muhammad Rahimi Yusop; Wan Nor Roslam Wan Isahak; Alinda Samsuri (Environmental Science and Pollution Research, 2024)

Spatiotemporal analyses of temperature and equivalent temperature and their relationship with crop health across Pakistan’s cropland - Muhammad Latif; Momel Zoon; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi; Rashed Mahmood; Muhammad Umar (Theoretical and Applied Climatology, 2024)

Modeling spatial distribution of earthquake epicenters using inhomogeneous Log-Gaussian Cox point process - Salma Anwar; Muhammad Yaseen; Muhammad Yaseen; Yasir Latif (Modeling Earth Systems and Environment, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

Biological response of red palm weevil (Rhynchophorus ferrugineus, Olivier) (Coleoptera: Curculionidae) on six different varieties of date palm - Gul Rehman; Muhammad Mamoon-ur-Rashid; Habib Ali; Mirza Abdul Qayyum; Shahbaz Ali; Muhammad Ali; Obaid Ullah Sayal; Asif Latif; Asghar Ali Khan (International Journal of Tropical Insect Science, 2024)

Understanding the origin of ancient carbonate ooids: recent findings - Muhammad Riaz; Santanu Banerjee; Khalid Latif; Ziliang Liu; Mohamed S. Ahmed; Douaa Fathy (International Geology Review, 2024)

Carbon trade-off and energy budgeting under conventional and conservation tillage in a rice-wheat double cropping system - Naeem Ahmad; Ahmad Latif Virk; Abdul-Sattar Nizami; Rattan Lal; Scott X. Chang; Muhammad Bilal Hafeez; Xingyu Guo; Rui Wang; Xiaoli Wang; Hafiz Muhammad Waleed Iqbal; Gadah Albasher; Jun Li (Journal of Environmental Management, 2024)

Fundamental opportunities and challenges of nutraceutical noodles enriched with agri-food by-products - Zahoor Ahmed; Jin Chen; Tabussam Tufail; Anam Latif; Muhammad Arif; Riaz Ullah; Ali S. Alqahtani; Bin Xu (Trends in Food Science & Technology, 2024)

Advanced nanomaterials and metal-organic frameworks for catalytic bio-diesel production from microalgal lipids – A review - Zohaib Saddique; Muhammad Imran; Shoomaila Latif; Ayesha Javaid; Shahid Nawaz; Nemira Zilinskaite; Marcelo Franco; Ausra Baradoke; Ewa Wojciechowska; Grzegorz Boczkaj (Journal of Environmental Management, 2024)

Genome-wide identification and characterization of wall-associated kinases, molecular docking and polysaccharide elicitation of monoterpenoid indole alkaloids in micro-propagated Catharanthus roseus - Jawad Ahmed; Yasar Sajjad; Aasia Latif; Mohammad Saeed Lodhi; Muhammad Huzafa; Chen Situ; Raza Ahmad; Muhammad Maroof Shah; Amjad Hassan (Journal of Plant Research, 2024)

Characterizing the HMA gene family in dragon fruit (Selenicereus undatus L.) and revealing their response to multifactorial stress combinations and melatonin-mediated tolerance - Qamar U Zaman; Latif Ullah Khan; Muhammad Azhar Hussain; Asif Ali; Liu Hui; Aamir Ali Khokhar; Darya Khan; Hua-Feng Wang (South African Journal of Botany, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Geocellular Modeling of the Cambrian to Eocene Multi-Reservoirs, Upper Indus Basin, Pakistan - Muhsan Ehsan; Muhammad Ali Umair Latif; Abid Ali; Ahmed E. Radwan; Muhammad Attique Amer; Kamal Abdelrahman (Natural Resources Research, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Engineering of Chlamydomonas reinhardtii chloroplast for mucosal immunotherapeutic against Newcastle disease virus - Sania Naeem; Naila Shahid; Mohsin Ahmad Khan; Saira Azam; Muhammad Saad Bhutta; Ayesha Latif; Aneela Yasmeen; Tahir Rehman Sami Ullah; Abdul Qayyum Rao; Kausar Malik (Journal of Applied Phycology, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

3D printing of concentrated nanocellulose material: The critical role of substrates on the shape fidelity and mechanical properties - Muhammad Latif; Yangxiaozhe Jiang; Jaehwan Kim (Carbohydrate Polymers, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Examining the energy trilemma index and the prospects for clean energy development - Meijing Song; Muhammad Irfan Latif; Jinjun Zhang; Mohamed Omran (Gondwana Research, 2023)

Anxiolytic-like effect of succinic acid: A possible GABAergic intervention - Md. Nayem Mia; Shanita Zaman Smrity; Mehedi Hasan Bappi; Hossam Kamli; Tawhida Islam; Abdullah Al Shamsh Prottay; Md. Showkoth Akbor; Md. Abdul Latif; Shoriful Islam; Kushal Bhakta; Manik Chandra Shill; Francisco Claudeni Pereira de Sousa; et al. (Food Bioscience, 2023)

Biohermal complex dominated by microbial carbonates from the early Miaolingian (lower Cambrian) Maozhuang Formation, North China - Mingxiang Mei; Muhammad Riaz; Khalid Latif; Ziliang Liu; Mohamed S. Ahmed; Douaa Fathy (Facies, 2023)

Date Palm Biochar and Date Palm Activated Carbon as Green Adsorbent—Synthesis and Application - Mona Al Malki; Abu Zahrim Yaser; Mohd. Amir Asyraf Mohd. Hamzah; Muhammad Abbas Ahmad Zaini; Nurzila Ab. Latif; Siti Halimah Hasmoni; Zainul Akmar Zakaria (Current Pollution Reports, 2023)

Evaluating the effects of soil physicochemical properties under different land use types in the arid zones of Pakistan - Muhammad Yaseen; Sohail Abbas; Yasir Latif (Environment, Development and Sustainability, 2023)

RETRACTED: Degradation of cefadroxil drug by newly designed solar light responsive alcoholic template-based lanthanum ferrite nanoparticles - Ammara Nazir; Muhammad Imran; Farah Kanwal; Shoomaila Latif; Ayesha Javaid; Tak H. Kim; Grzegorz Boczkaj; Ashwag Shami; Hafiz Iqbal (Environmental Research, 2023)

Phytohormones Mediated Modulation of Abiotic Stress Tolerance and Potential Crosstalk in Horticultural Crops - Muhammad Ahsan Altaf; Rabia Shahid; Ravinder Kumar; Muhammad Mohsin Altaf; Awadhesh Kumar; Latif Ullah Khan; Muhammad Saqib; Muhammad Azher Nawaz; Bushra Saddiq; Saraj Bahadur; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

Multifunctional catalyst-assisted sustainable reformation of lignocellulosic biomass into environmentally friendly biofuel and value-added chemicals - Muhammad Naeem; Muhammad Imran; Shoomaila Latif; Adnan Ashraf; Nazim Hussain; Grzegorz Boczkaj; Wojciech Smułek; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Bio-fabricated bismuth-based materials for removal of emerging environmental contaminants from wastewater - Zohaib Saddique; Muhammad Imran; Ayesha Javaid; Shoomaila Latif; Tak H. Kim; Marcin Janczarek; Muhammad Bilal; Teofil Jesionowski (Environmental Research, 2023)

Correction to: Assessment of potentially toxic metal(loid)s contamination in soil near the industrial landfill and impact on human health: an evaluation of risk - Waqar Ahmad; Muhammad Zubair; Mahmood Ahmed; Muhammad Ahmad; Shoomaila Latif; Abdul Hameed; Qudsia Kanwal; Dure Najaf Iqbal (Environmental Geochemistry and Health, 2023)

Assessment of potentially toxic metal(loid)s contamination in soil near the industrial landfill and impact on human health: an evaluation of risk - Waqar Ahmad; Muhammad Zubair; Mahmood Ahmed; Muhammad Ahmad; Shoomaila Latif; Abdul Hameed; Qudsia Kanwal; Dure Najaf Iqbal (Environmental Geochemistry and Health, 2023)

The presence of polycyclic aromatic hydrocarbons (PAHs) in air particles and estimation of the respiratory deposition flux - Nur Ain Nazirah Binti Najurudeen; Md Firoz Khan; Hamidah Suradi; Ummay Ayesha Mim; Israt Nur Janntul Raim; Sara Binte Rashid; Mohd Talib Latif; Muhammad Nurul Huda (Science of The Total Environment, 2023)

Investigating resource curse/blessing hypothesis: An empirical insights from Luxembourg, the Netherlands, and Portugal economies - Shengming Chen; Muhammad Shahid Hassan; Ayesha Latif; Abdul Rafay; Haider Mahmood; Xiaowei Xu (Resources Policy, 2023)

The solar end game: bibliometric analysis, research and development evolution, and patent activity of hybrid photovoltaic/thermal—phase change material - Muhammad Hussin Abdul Jabar; Rishita Srivastava; Norhuda Abdul Manaf; Suchithra Thangalazhy-Gopakumar; Farah Ezzah Ab Latif; Minh Tri Luu; Ali Abbas (Environmental Science and Pollution Research, 2023)

First report of clover yellow vein virus infecting Pisum sativum in China - Jinlong Yin; Jingquan Tan; Sha Luo; Xin Hong; Yuanming Zhang; Yangling Qiu; Muhammad Faizan Latif; Kai Xu (Journal of Plant Pathology, 2023)

Tissue specific expression of bacterial cellulose synthase (Bcs) genes improves cotton fiber length and strength - Sidra Akhtar; Ahmad Ali Shahid; Sana Shakoor; Mukhtar Ahmed; Sehrish Iftikhar; Muhammad Usmaan; Sahar Sadaqat; Ayesha Latif; Adnan Iqbal; Abdul Qayyum Rao (Plant Science, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

Green surface functionalization of chitosan with spent tea waste extract for the development of an efficient adsorbent for aspirin removal - Abu Hassan Nordin; Norzita Ngadi; Rushdan Ahmad Ilyas; Nur Aien Fatini Abd Latif; Muhammad Luqman Nordin; Mohd Syahlan Mohd Syukri; Walid Nabgan; Syafikah Huda Paiman (Environmental Science and Pollution Research, 2023)

Unraveling the mutualistic interaction between endophytic Curvularia lunata CSL1 and tomato to mitigate cadmium (Cd) toxicity via transcriptomic insights - Sajjad Asaf; Rahmatullah Jan; Muhammad Aaqil Khan; Lubna; Abdul Latif Khan; Saleem Asif; Saqib Bilal; Waqar Ahmad; Muhammad Waqas; Kyung-Min Kim; Ahmed AL-Harrasi; In-Jung Lee (Science of The Total Environment, 2023)

Do green entrepreneurial orientation and green knowledge management matter in the pursuit of ambidextrous green innovation: A moderated mediation model - Muhammad Usman Shehzad; Jianhua Zhang; Khawaja Fawad Latif; Khalid Jamil; Abdul Hakeem Waseel (Journal of Cleaner Production, 2023)

Adsorption modeling and thermodynamic characteristics of silver ions on to low-rank Pakistani coal - Tariq Javed; Nasir Khalid; Muhammad Latif Mirza (Sustainable Water Resources Management, 2023)

CRISPR/Cas9-mediated genome editing in diploid and tetraploid potatoes - Aneela Yasmeen; Allah Bakhsh; Sara Ajmal; Momna Muhammad; Sahar Sadaqat; Muhammad Awais; Saira Azam; Ayesha Latif; Naila Shahid; Abdul Qayyum Rao (Acta Physiologiae Plantarum, 2023)

Reuse of waste cooking oil (WCO) as diluent in green emulsion liquid membrane (GELM) for zinc extraction - Afiqah Tasneem Abd Khalil; Meor Muhammad Hafiz Shah Buddin; Siti Wahidah Puasa; Abdul Latif Ahmad (Environmental Science and Pollution Research, 2023)

Tracking depositional and geochemical variations in the Cambrian North China Platform: Insights from sedimentology, geochemistry, and C-O isotopic records - Muhammad Riaz; Arman Jafarian; Ardiansyah Koeshidayatullah; Fabrizio Frontalini; Lei Jiang; Khalid Latif; Tehseen Zafar (Sedimentary Geology, 2023)

Development of zinc ferrite nanoparticles with enhanced photocatalytic performance for remediation of environmentally toxic pharmaceutical waste diclofenac sodium from wastewater - Shoomaila Latif; Amna Liaqat; Muhammad Imran; Ayesha Javaid; Nazim Hussain; Teofil Jesionowski; Muhammad Bilal (Environmental Research, 2023)

Cow bone-derived biochar enhances microbial biomass and alters bacterial community composition and diversity in a smelter contaminated soil - Muhammad Azeem; Parimala Gnana Soundari Arockiam Jeyasundar; Amjad Ali; Luqman Riaz; Khalid S. Khan; Qaiser Hussain; Hafiz A. Kareem; Fakhar Abbas; Abdul Latif; Ali Majrashi; Esmat F. Ali; Ronghua Li; et al. (Environmental Research, 2023)

Subsurface groundwater aquifer mapping and quality characterization in Matiari district, Sindh, Pakistan - Rabia Dars; Abdul Latif Qureshi; Muhammad Afzal Jamali; Hafiz Abdul Salam Memon; Shafi Muhammad Kori; Shamotra Oad (Environmental Monitoring and Assessment, 2023)

Protective Mechanisms of Melatonin Against Vanadium Phytotoxicity in Tomato Seedlings: Insights into Nutritional Status, Photosynthesis, Root Architecture System, and Antioxidant Machinery - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Latif Ullah Khan; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Muhammad Azher Nawaz; Safina Naz; Sidra Shahid; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Adnan Shahid (Journal of Plant Growth Regulation, 2022)

Abundance of natural resources and environmental sustainability: the roles of manufacturing value-added, urbanization, and permanent cropland - Zahid Zahoor; Muhammad Irfan Latif; Irfan Khan; Fujun Hou (Environmental Science and Pollution Research, 2022)

Subsurface depleting aquifers in the sedimentary terrain of Quetta Valley in Balochistan: a review - Abdul Latif Qureshi; Muhammad Afzal Jamali; Shahzad Hussain; Farhad Ali Memon; Arjumand Zahra Zaidi; Sumaira Zafar; Waqas Ahmed (Arabian Journal of Geosciences, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Biosorption potential and molecular characterization of metal-resistant autochthonous microbes from tannery solid waste - Hajira Younas; Aisha Nazir; Zakia Latif; Janice E. Thies; Muhammad Shafiq; Firdaus-e- Bareen (Archives of Microbiology, 2022)

Side-Scan Sonar Coupled with Scuba Diving Observation for Enhanced Monitoring of Benthic Artificial Reefs along the Coast of Terengganu, Peninsular Malaysia - Azizi Ali; Muhammad Ruzi Abdullah; Che Din Mohd Safuan; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok; Mohd Fadzil Mohd Akhir; Roslan Latif; Azri Muhamad; Tan Hock Seng; Adina Roslee; Khaira Ismail (Journal of Marine Science and Engineering, 2022)
Since the 1970s, artificial reef (AR) deployment has been one of the common approaches to augment the local production of coastal fish in Malaysia. However, there is a lack of strategy to assess and evaluate the success of pre-deployed AR. Realizing the need for an effective qualitative and quantitative monitoring and evaluation of AR, this study proposes side-scan sonar coupled with scuba diving observation for the enhanced monitoring of pre-deployed Bioceramic Korean (BK) AR along the coast of Terengganu, Peninsular Malaysia. This method employs an integrated side-scan sonar with a data acquisition system for the detection of the precise location of the BK AR which were deployed at Tukun Telaga Batin off the Terengganu coastline in 2003 by the Fisheries Development Authority of Malaysia (FDAM). Following the determination of the exact location of three BK AR areas, a scuba diving team was sent to survey the physical conditions of the AR and assess the feasibility of the AR as an artificial habitat for marine life. The scan sonar images were compared with the captured photographs and videos acquired during the scuba diving session for a comprehensive value-added assessment. The collected data from the scuba diving session were also processed to measure the fish diversity, the fish biomass, and identify the fish community surrounding the AR. Based on the results, the BK AR remained in extremely good condition, physically intact, without significant breakage or damage, and with no major subsidence into the sediment after 19 years of deployment. A total of 108 BK AR modules were detected in three large groups using the mosaicked sonar images. Following cross-examination to validate the AR measurements using the AR’s shadows on the seafloor, the height of the BK AR consistently ranged from 1.7 m to 1.8 m. In addition, 34 species of fish from 14 families and 26 genera were identified, with most species classified as reef-associated (RA) fish with a biomass value of 1173.31 ± 1136.69 kg m−3, indicating the successfulness of the BK AR as fish-aggregating devices (FADs). The growth of hard corals on top of the bioceramic plate of the AR module further supported the diversified community of marine life surrounding the BK AR. In conclusion, the side-scan sonar coupled with scuba diving observation demonstrates an effective qualitative and quantitative technique for the monitoring and evaluation of pre-deployed AR. This strategy is recommended to be utilized to determine the success of pre-deployment AR.

Mapping of marine lobster research: A global outlook - Mohamad Nor Azra; Mok Wen Jye; Hien Van Doan; Ivar Zekker; Muhammad Fuad Abdullah; Zulkiflee Abd Latif; Mohd Iqbal Mohd Noor (Frontiers in Marine Science, 2022)
This study examined research and development of the commercially important marine lobster, in terms of descriptive metadata and scientometric analysis. We consider a collection of over 9,578 related articles to assess literature patterns and research development trends related to marine lobsters as a topic. Web of Science Core Collection was used to identify, collate, and generate publication trends, a list prominent authors and affiliations involved, countries that actively participated, and the co-citation analysis of the references as well as impactful articles and keywords. There were 149 different countries or states that had relevant publications on lobster research. We found an increase in the number of publications over time, with the USA having the most number of publications, followed by Australia and Canada. A total of 17,782 authors were involved in the field of lobster studies. Canadian researchers had the highest citation count for marine lobster research. Surprisingly, the most impactful keyword was crayfish, followed by neuron and amino acid sequence. Our study identifies the multidisciplinary nature in marine lobster research, which includes fields such as neuroscience and developmental genetics. We find that lobster scientific publications increasingly center on the broader coverage areas of science such as taxonomy and basic biology.

CRISPR-Cas9 based stress tolerance: New hope for abiotic stress tolerance in chickpea (Cicer arietinum) - Muhammad Khuram Razzaq; Muhammad Akhter; Ramala Masood Ahmad; Kaiser Latif Cheema; Aiman Hina; Benjamin Karikari; Ghulam Raza; Guangnan Xing; Junyi Gai; Mohsin Khurshid (Molecular Biology Reports, 2022)

Antioxidant, antimicrobial, enzyme inhibition, and cytotoxicity guided investigation of Sideroxylon mascatense (A.DC.) T.D. Penn. leaves extracts - Joham Sarfraz Ali; Naheed Riaz; Abdul Mannan; Muhammad Latif; Muhammad Zia (Natural Product Research, 2022)

Performance evaluation and comparison of observed and reanalysis gridded precipitation datasets over Pakistan - Sayed Waseem Iqbal; Muhammad Latif; Rehan Ahmed; Shahzada Adnan; Muhammad Umar; Burhan Ahmad; Muhammad Azam; Jabir Hussain Syed (Theoretical and Applied Climatology, 2022)

Understanding the dynamics of natural resources rents, environmental sustainability, and sustainable economic growth: new insights from China - Hafiz Muhammad Arslan; Irfan Khan; Muhammad Irfan Latif; Bushra Komal; Songsheng Chen (Environmental Science and Pollution Research, 2022)

Integrated application of plant bioregulator and micronutrients improves crop physiology, productivity and grain biofortification of delayed sown wheat - Naeem Ahmad; Ahmad Latif Virk; Sadam Hussain; Muhammad Bilal Hafeez; Fasih Ullah Haider; Muhammad Ishaq Asif Rehmani; Tauqeer Ahmad Yasir; Ariba Asif (Environmental Science and Pollution Research, 2022)

Bionomics and management of aphid, Brevicoryne brassicae (Homoptera: Aphididae) on canola (Brassica napus) using Chrysoperla carnea - Muhammad Mamoon-ur-Rashid; Syed Wajhi-ul-Abbas; Habib Ali; Hussan Ara Beghum; Waqar Islam; Madiha Zaynab; Mubasher Hussain; Obaid Ullah Sayal; Habib ur Rehman; Asif Latif (International Journal of Tropical Insect Science, 2022)

Salicylic Acid Induces Vanadium Stress Tolerance in Rice by Regulating the AsA-GSH Cycle and Glyoxalase System - Muhammad Mohsin Altaf; Xiao-ping Diao; Haihua Wang; Latif Ullah Khan; Atique ur Rehman; Awais Shakoor; Muhammad Ahsan Altaf; Taimoor Hassan Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Nerolidol: a potential approach in rheumatoid arthritis through reduction of TNF-α, IL-1β, IL-6, NF-kB, COX-2 and antioxidant effect in CFA-induced arthritic model - Shanila Akhter; Hafiz Muhammad Irfan; Alamgeer; Shah Jahan; Muhammad Shahzad; Muhammad Bilal Latif (Inflammopharmacology, 2022)

Melatonin Mitigates Cadmium Toxicity by Promoting Root Architecture and Mineral Homeostasis of Tomato Genotypes - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Safina Naz; Muhammad Mohsin Altaf; Latif Ullah Khan; Milan Kumar Lal; Rahul Kumar Tiwari; Awais Shakoor (Journal of Soil Science and Plant Nutrition, 2022)

Delineating Vanadium (V) Ecological Distribution, Its Toxicant Potential, and Effective Remediation Strategies from Contaminated Soils - Muhammad Mohsin Altaf; Xiao-ping Diao; Awais Shakoor; Muhammad Imtiaz; Atique-ur-Rehman; Muhammad Ahsan Altaf; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2022)

Sequence stratigraphy, depositional and diagenetic environments of the late Cambrian glauconite bearing oolitic limestones in the Kelan Section, Shanxi, China - Muhammad Riaz; G M Bhat; Khalid Latif; Tehseen Zafar; Shahid Ghazi (Journal of Earth System Science, 2022)

Morphology and genesis of the Cambrian oncoids in Wuhai Section, Inner Mongolia, China - Muhammad Riaz; Khalid Latif; Tehseen Zafar; Enzhao Xiao; Shahid Ghazi (Carbonates and Evaporites, 2022)

Illuminating Empirical Evidence of Climate Change: Impacts on Rice Production in the Punjab Regions, Pakistan - Sohail Abbas; Shazia Kousar; Safdar Ali Shirazi; Muhammad Yaseen; Yasir Latif (Agricultural Research, 2022)

Removal of emerging contaminants by emulsion liquid membrane: perspective and challenges - Nur Dina Zaulkiflee; Abdul Latif Ahmad; Nuur Fahanis Che Lah; Meor Muhammad Hafiz Shah Buddin (Environmental Science and Pollution Research, 2022)

Climatology of dust storm frequency and its association with temperature and precipitation patterns over Pakistan - Mehwish Aziz Dar; Rehan Ahmed; Muhammad Latif; Muhammad Azam (Natural Hazards, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Implication of Remote Sensing Data under GIS Environment for Appraisal of Irrigation System Performance - Sultan Ahmad Rizvi; Afeef Ahmad; Muhammad Latif; Abdul Sattar Shakir; Aftab Ahmad Khan; Waqas Naseem; Muhammad Riaz Gondal (Water Resources Management, 2021)

RETRACTED ARTICLE: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2021)

Characterization of Mercury-Resistant Rhizobacteria for Plant Growth Promotion: An In Vitro and In Silico Approach - Aatif Amin; Muhammad Naveed; Umair Munawar; Arslan Sarwar; Zakia Latif (Current Microbiology, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Convective available potential energy (CAPE) in Pakistan and its association with precipitation and temperature - Sameen Malik; Rehan Ahmed; Muhammad Latif; Muhammad Azam; Ehsan Haroon; Muhammad Bilal Iqbal (Theoretical and Applied Climatology, 2021)

Melatonin Mitigates Nickel Toxicity by Improving Nutrient Uptake Fluxes, Root Architecture System, Photosynthesis, and Antioxidant Potential in Tomato Seedling - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2021)

Sorptive Capture and Photo-Catalytic Degradation of Methylene Blue from Aqueous Solution Using Lead-Organic Frameworks - Shoomaila Latif; Shamaila Iram; Muhammad Imran; Farah Kanwal; Zafar Iqbal; Aisha Batool; Liviu Mitu (Water, Air, & Soil Pollution, 2021)

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

Effect of plant spacing on incidence of rice planthoppers in transplanted rice crop - Muhammad Asghar; Talfoor-ul Hassan; Muhammad Arshad; Asif Aziz; Muhammad Tahir Latif; Arshed Makhdoom Sabir (International Journal of Tropical Insect Science, 2021)

Rising Metals Concentration in the Environment: A Response to Effluents of Leather Industries in Sialkot - Noreen Khalid; Zarrin Fatima Rizvi; Nousheen Yousaf; Shujaul Mulk Khan; Ali Noman; Muhammad Aqeel; Komal Latif; Asmara Rafique (Bulletin of Environmental Contamination and Toxicology, 2021)

Physicomechanical, stability, and pharmacokinetic evaluation of aceclofenac dimethyl urea cocrystals - Hafsa Afzal; Nasir Abbas; Amjad Hussain; Sumera Latif; Kanwal Fatima; Muhammad Sohail Arshad; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2021)

Relationship between adaptation to climate change and provincial government expenditure in Pakistan - Khuda Bakhsh; Aasma Latif; Rafaqet Ali; Muhammad Asim Yasin (Environmental Science and Pollution Research, 2021)

Managing organic carbon of sandy clay loam soil with organic amendments to promote particle aggregation - Haroon Shahzad; Muhammad Iqbal; Noman Latif; Muhammad Arshad Khan; Qudrat Ullah Khan (Arabian Journal of Geosciences, 2021)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

Oral supplementation of Ficus religiosa leaf extract adversely affects the selected behavioral aspects of male albino mice - Naheed Akhtar; Shahid Iqbal; Muhammad Faisal Shahzad; Muhammad Latif; Furhan Iqbal (Biologia, 2020)

Current findings on carp edema virus, control challenges, and future outlook - Tayyab Rehman; Lizi Yin; Muhammad Bilal Latif; Yaojia Zhou; Kaiyu Wang; Yi Geng; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Hongrui Guo; Weiming Lai; et al. (Aquaculture International, 2020)

Petrographic and rare earth elemental characteristics of Cambrian Girvanella oncoids exposed in the North China Platform: Constraints on forming mechanism, REE sources, and paleoenvironments - Muhammad Riaz; Tehseen Zafar; Khalid Latif; Shahid Ghazi; Enzhao Xiao (Arabian Journal of Geosciences, 2020)

A novel nonsense mutation in NPR2 gene causing Acromesomelic dysplasia, type Maroteaux in a consanguineous family in Southern Punjab (Pakistan) - Saima Mustafa; Zafrin Akhtar; Muhammad Latif; Mubashir Hassan; Muhammad Faisal; Furhan Iqbal (Genes & Genomics, 2020)
Background Acromesomelic dysplasia, type Maroteaux (AMDM) is a rare skeletal dysplasia following autosomal recessive mode of inheritance and characterized by abnormal growth plates, short and abnormal bones in the extremities and spine. Objective Present study was designed to report the molecular basis of AMDM in enrolled consanguineous family from Pakistan. Methods A consanguineous family from Vehari District in Pakistan having multiple siblings suffering from AMDM was enrolled in present study. Whole exome sequencing (WES) approach was adopted to identify causative agent of AMDM. Human full length NPR2 gene and sequence with nonsense mutation was amplified by using Myc-tagged pXN vector and transformed in E. coli DH5α cells to confirm mutation. SDS-PAGE and Western blotting were done to confirm the production of truncated protein. Computational three dimensional structure generation through homology modeling approach was done to compare protein structure between patients and controls. Results WES reveled a nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene leading to premature termination codon in mRNA of NPR2 gene resulting in a truncated protein with 204 amino acid residues that was confirmed by SDS-PAGE and Western blotting. Sanger sequencing confirmed that mutation in all subjects and mutation followed Mendalian pattern of inheritance. Multiple sequence alignment by ClustalW revealed that mutated domain of NPR2 is conserved region. Proetin structure comparison revealed a significant structural part of NPR2 was missing in truncated protein as compared to control. Conclusion We are reporting that a novel nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene is causing AMDM in a consanguineous Pakistani family.

Effect of reservoir models and climate change on flood analysis in arid regions - Ahmed samy Kamis; Abdullah Al-Wagdany; Jarbou Bahrawi; Muhammad Latif; Amro Elfeki; Abdel Hannachi (Arabian Journal of Geosciences, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Efficacy of Alternanthera bettzickiana to Remediate Copper and Cobalt Contaminated Soil Physiological and Biochemical Alterations - Amna Khalid; Mujahid Farid; Muhammad Zubair; Muhmmad Rizwan; Usman Iftikhar; Hafiz Khuzama Ishaq; Sheharyaar Farid; Urousa Latif; Kiran Hina; Shafaqat Ali (International Journal of Environmental Research, 2020)

First report of leaf spots in Caryota mitis L. caused by Alternaria alstroemeriae in Pakistan - Imran Ul haq; Siddra Ijaz; Anjum Faraz; Muhammad Kaleem Sarwar; Muhammad Zunair Latif; Nabeeha Aslam Khan (Journal of Plant Pathology, 2020)

Impact of jet stream and associated mechanisms on winter precipitation in Pakistan - Fayyaz Ahmed; Shahzada Adnan; Muhammad Latif (Meteorology and Atmospheric Physics, 2020)

Spatial analysis of temperature time series over the Upper Indus Basin (UIB) Pakistan - Yasir Latif; Ma Yaoming; Muhammad Yaseen; Sher Muhammad; Muhammad Atif Wazir (Theoretical and Applied Climatology, 2020)
Runoff generated from the Upper Indus Basin (UIB) mainly originates in the massifs of the Hindukush–Karakoram–Himalaya (HKH) region of Pakistan. Water supply in early spring depends upon the snow accumulation in the winter and the subsequent temperature. Seasonal temperature variations corroborate the contemporary dynamics of snow and glaciers. Recently, there has been increasing evidence of accelerated warming in high mountain areas, termed as elevation-dependent warming (EDW). We have identified trends, analyzed inconsistencies, and calculated changes in the maximum, minimum, mean and diurnal temperature range ( T max , T min , T mean , and DTR) at 20 weather stations during four-time series: 1961–2013 (first), 1971–2013 (second), 1981–2013 (third), and 1991–2013 (fourth). We employed the Mann–Kendall test to determine the existence of a trend and Sen’s method for the estimation of prevailing trends, whereas homogeneity analysis was applied before trend identification using three different tests. This study revealed that the largest and smallest magnitudes of trends appeared in the winter and summer, respectively, particularly during the fourth data series. T max revealed robust warming at ten stations, most remarkably at Gupis, Khunjrab, and Naltar at rates of 0.29, 0.36, and 0.43 °C/decade, respectively, during the fourth series. We observed that T min exhibits a mixed pattern of warming and cooling during the second and third series, but cooling becomes stronger during the fourth series, exhibiting significant trends at twelve stations. Khunjrab and Naltar showed steady warming during the fourth series (spring), at rates of 0.26 and 0.13 °C/decade in terms of T mean . The observed decreases in DTR appeared stronger in the fourth series during the summer. These findings tend to partially support the notion of EDW but validate the dominance of cooling spatially and temporally.

Antibiotics in poultry manure and their associated health issues: a systematic review - Juma Muhammad; Sardar Khan; Jian Qiang Su; Abd El-Latif Hesham; Allah Ditta; Javed Nawab; Abid Ali (Journal of Soils and Sediments, 2020)

Assessment of noise pollution and its effects on human health in industrial hub of Pakistan - Zia Ur Rahman Farooqi; Muhammad Sabir; Junaid Latif; Zubair Aslam; Hamaad Raza Ahmad; Iftikhar Ahmad; Muhammad Imran; Predrag Ilić (Environmental Science and Pollution Research, 2020)

Spatiotemporal trends in reference evapotranspiration over South Korea - Ju Ha Hwang; Muhammad Azam; Maeng Seung Jin; Yong Ho Kang; Jae Eun Lee; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Muhammad Zaffar Hashmi (Paddy and Water Environment, 2020)

Assessment of groundwater potential through vertical electrical sounding at Haji Rehmatullah Palari village, Nooriabad - Asadullah Soomro; Abdul Latif Qureshi; Muhammad Afzal Jamali; Arshad Ashraf; Asfand Yar Wali Arain (Acta Geophysica, 2019)

Calcified cyanobacteria fossils from the leiolitic bioherm in the Furongian Changshan Formation, Datong (North China Platform) - Khalid Latif; Enzhao Xiao; Muhammad Riaz; Abdullah Ali Ali Hussein (Carbonates and Evaporites, 2019)

Thunderstorm frequency distribution and associated convective mechanisms over Pakistan - Rehan Ahmed; Muhammad Latif; Shahzada Adnan; Muhammad Khubaib Abuzar (Theoretical and Applied Climatology, 2019)

Effects of biochar and NPK on soil microbial biomass and enzyme activity during 2 years of application in the arid region - Muhammad Azeem; Rifat Hayat; Qaiser Hussain; Muhammad Ibrahim Tahir; Muhammad Imran; Zafar Abbas; Muhammad Sajid; Abdul Latif; Muhammad Irfan (Arabian Journal of Geosciences, 2019)

Growth-promoting bioactivities of Bipolaris sp. CSL-1 isolated from Cannabis sativa suggest a distinctive role in modifying host plant phenotypic plasticity and functions - Lubna; Sajjad Asaf; Abdul Latif Khan; Muhammad Waqas; Sang-Mo Kang; Muhammad Hamayun; In-Jung Lee; Anwar Hussain (Acta Physiologiae Plantarum, 2019)

IL-22 in hepatocyte’s survival of Pakistani patients with end stage liver disease: an insight into IL 22 mediated hepato-regenerative pathway - Muhammad Saalim; Saleha Resham; Sobia Manzoor; Hassam Ahmad; Tariq Ali Bangash; Amir Latif; Shahla Jaleel (Molecular Biology Reports, 2019)

Groundwater investigation through vertical electrical sounding at hilly area from Nooriabad toward Karachi - Asadullah Soomro; Abdul Latif Qureshi; Muhammad Afzal Jamali; Arshad Ashraf (Acta Geophysica, 2019)

Halo-tolerant rhizospheric Arthrobacter woluwensis AK1 mitigates salt stress and induces physio-hormonal changes and expression of GmST1 and GmLAX3 in soybean - Muhammad Aaqil Khan; Ihsan Ullah; Muhammad Waqas; Muhammad Hamayun; Abdul Latif Khan; Sajjad Asaf; Sang-Mo Kang; Kyung-Min Kim; Rahmatullah Jan; In-Jung Lee (Symbiosis, 2019)

Yucca schidigera can mitigate ammonia emissions from manure and promote poultry health and production - Muhammad Saeed; Muhammad Asif Arain; Muhammad Naveed; Mahmoud Alagawany; Mohamed Ezzat Abd El-Hack; Zohaib Ahmed Bhutto; Marek Bednarczyk; Mohib Ullah Kakar; Mervat Abdel-Latif; Sun Chao (Environmental Science and Pollution Research, 2018)

Endophytic fungus Paecilomyces formosus LHL10 produces sester-terpenoid YW3548 and cyclic peptide that inhibit urease and α-glucosidase enzyme activities - Saqib Bilal; Liaqat Ali; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Sang-Mo Kang; Sang-Kuk Kim; In-Jung Lee (Archives of Microbiology, 2018)

Performance Evaluation of the Raised-Bed Planting and Potential in Improving Sugar Beet Yield and Water Use Efficiency in Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Latif; Muhammad Ajmal (Sugar Tech, 2018)

Simultaneously Improving Mechanical, Formulation, and In Vivo Performance of Naproxen by Co-Crystallization - Nasir Abbas; Sumera Latif; Hafsa Afzal; Muhammad Sohail Arshad; Amjad Hussain; Saleha Sadeeqa; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2018)

Sucrose synthase genes: a way forward for cotton fiber improvement - Mukhtar Ahmed; Ahmad Ali Shahid; Sidra Akhtar; Ayesha Latif; Salah ud Din; Ma Fanglu; Abdul Qayyum Rao; Muhammad Bilal Sarwar; Tayyab Husnain; Wang Xuede (Biologia, 2018)

Regulation of endogenous phytohormones and essential metabolites in frankincense-producing Boswellia sacra under wounding stress - Abdul Latif Khan; Ahmed Al-Harrasi; Raheem Shahzad; Qari Muhammad Imran; Byung-Wook Yun; Yoon-Ha Kim; Sang-Mo Kang; Ahmed Al-Rawahi; In-Jung Lee (Acta Physiologiae Plantarum, 2018)

Optimizing Irrigation Deficit of Multipurpose Cascade Reservoirs - Muhammad Usman Rashid; Abid Latif; Muhammad Azmat (Water Resources Management, 2018)

Spatial analysis of precipitation time series over the Upper Indus Basin - Yasir Latif; Ma Yaoming; Muhammad Yaseen (Theoretical and Applied Climatology, 2018)

Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Mohd Shahrul Mohd Nadzir; Matthew J. Ashfold; Md Firoz Khan; Andrew D. Robinson; Conor Bolas; Mohd Talib Latif; Benjamin M. Wallis; Mohammed Iqbal Mead; Haris Hafizal Abdul Hamid; Neil R. P. Harris; Zamzam Tuah Ahmad Ramly; Goh Thian Lai; et al. (Environmental Science and Pollution Research, 2018)

Marble industry effluents cause an increased bioaccumulation of heavy metals in Mahaseer (Tor putitora) in Barandu River, district Buner, Pakistan - Shahi Mulk; Abdul Latif Korai; Azizullah Azizullah; Lubna Shahi; Muhammad Nasir Khan Khattak (Environmental Science and Pollution Research, 2017)

Enzyme inhibitory metabolites from endophytic Penicillium citrinum isolated from Boswellia sacra - Sajid Ali; Abdul Latif Khan; Liaqat Ali; Tania Shamim Rizvi; Sumera Afzal Khan; Javid Hussain; Muhammad Hamayun; Ahmed Al-Harrasi (Archives of Microbiology, 2017)

Characterization of rainwater chemical composition after a Southeast Asia haze event: insight of transboundary pollutant transport during the northeast monsoon - Mohd Shahrul Mohd Nadzir; Chin Yik Lin; Md Firoz Khan; Mohd Talib Latif; Doreena Dominick; Haris Hafizal Abdul Hamid; Noorlin Mohamad; Khairul Nizam Abdul Maulud; Muhammad Ikram Abdul Wahab; Nurul Farahana Kamaludin; Mohamad Azwani Shah Mat Lazim (Environmental Science and Pollution Research, 2017)

Comparative study of performance of real-time satellite-derived rainfall in Swat Catchment - Muhammad Umar; Adil Latif; Syed Amer Mahmood (Arabian Journal of Geosciences, 2017)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Additive effects due to biochar and endophyte application enable soybean to enhance nutrient uptake and modulate nutritional parameters - Muhammad Waqas; Yoon-Ha Kim; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Hamayun; Sang-Mo Kang; Muhammad Aaqil Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2017)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Decreased fish diversity found near marble industry effluents in River Barandu, Pakistan - Shahi Mulk; Abdul Latif Korai; Azizullah Azizullah; Muhammad Nasir Khan Khattak (Ecotoxicology, 2016)

Mutualistic fungal endophytes produce phytohormones and organic acids that promote japonica rice plant growth under prolonged heat stress - Muhammad Waqas; Abdul Latif Khan; Raheem Shahzad; Ihsan Ullah; Abdur Rahim Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2015)

Escherichia coli expression of NDV fusion protein gene and determination of its antigenic epitopes - Naila Shahid; Sana Tahir; Abdul Q. Rao; Sameera Hassan; Anwar Khan; Ayesha Latif; Muhammad Au Khan; Bushra Tabassum; Ahmed A. Shahid; Ahmed U. Zafar; Tayyab Husnain (Biologia, 2015)

Improvement in phytoremediation potential of Solanum nigrum under cadmium contamination through endophytic-assisted Serratia sp. RSC-14 inoculation - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Gun-Seok Park; Muhammad Waqas; Sung-Jun Hong; Byung Kwon Jung; Yunyoung Kwak; In-Jung Lee; Jae-Ho Shin (Environmental Science and Pollution Research, 2015)

Synthesis and evaluation of unsymmetrical heterocyclic thioureas as potent β-glucuronidase inhibitors - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Khalid Mohammed Khan; Uzma Salar; Syed Muhammad Kashif; Fazal Rahim; Yawar Latif (Medicinal Chemistry Research, 2015)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Endophytic infection alleviates biotic stress in sunflower through regulation of defence hormones, antioxidants and functional amino acids - Muhammad Waqas; Abdul Latif Khan; Muhammad Hamayun; Raheem Shahzad; Yoon-Ha Kim; Kyung-Sook Choi; In-Jung Lee (European Journal of Plant Pathology, 2015)

Resilience of Penicillium resedanum LK6 and exogenous gibberellin in improving Capsicum annuum growth under abiotic stresses - Abdul Latif Khan; Muhammad Waqas; In-Jung Lee (Journal of Plant Research, 2015)

Impact of marble industry effluents on water and sediment quality of Barandu River in Buner District, Pakistan - Shahi Mulk; Azizullah Azizullah; Abdul Latif Korai; Muhammad Nasir Khan Khattak (Environmental Monitoring and Assessment, 2015)

Synthesis, docking studies, and in silico ADMET predictions of some new derivatives of pyrimidine as potential KSP inhibitors - Umer Rashid; Syed Fahad Hassan; Samina Nazir; Abdul Wadood; Muhammad Waseem; Farzana Latif Ansari (Medicinal Chemistry Research, 2015)

Phytostabilization and Physicochemical Responses of Korean Ecotype Solanum nigrum L. to Cadmium Contamination - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Sung-Jun Hong; Muhammad Waqas; Gun-Seok Park; Yunyoung Kwak; JungBae Choi; Byung-Kwon Jung; Man Park; In-Jung Lee; Jae-Ho Shin (Water, Air, & Soil Pollution, 2014)

Phytohormone-producing fungal endophytes and hardwood-derived biochar interact to ameliorate heavy metal stress in soybeans - Muhammad Waqas; Abdul Latif Khan; Sang-Mo Kang; Yoon-Ha Kim; In-Jung Lee (Biology and Fertility of Soils, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

Silicon Application to Rice Root Zone Influenced the Phytohormonal and Antioxidant Responses Under Salinity Stress - Yoon Ha Kim; Abdul Latif Khan; Muhammad Waqas; Jae Kyoung Shim; Duck Hwan Kim; Kyeong Yeoll Lee; In Jung Lee (Journal of Plant Growth Regulation, 2014)

Regulation of endogenous gibberellins and abscisic acid levels during different seed collection periods in Panax ginseng - Yoon-Ha Kim; In-Ok Ahn; Abdul Latif Khan; Muhammad Kamran; Muhammad Waqas; Joon-Soo Lee; Duk-Hwan Kim; Soo-Won Jang; In-Jung Lee (Horticulture, Environment, and Biotechnology, 2014)

Identification of recurrent c.742G>T nonsense mutation in ECM1 in Pakistani families suffering from lipoid proteinosis - Muhammad Nasir; Simeen Ber Rahman; Christian M. K. Sieber; Asif Mir; Amir Latif; Nafees Ahmad; Salman Akbar Malik; Abdul Hameed (Molecular Biology Reports, 2014)

Fungal endophyte Penicillium janthinellum LK5 can reduce cadmium toxicity in Solanum lycopersicum (Sitiens and Rhe) - Abdul Latif Khan; Muhammad Waqas; Javid Hussain; Ahmed Al-Harrasi; In-Jung Lee (Biology and Fertility of Soils, 2014)

Fungal endophyte Penicillium janthinellum LK5 improves growth of ABA-deficient tomato under salinity - Abdul Latif Khan; Muhammad Waqas; Abdur Rahim Khan; Javid Hussain; Sang-Mo Kang; Syed Abdullah Gilani; Muhammad Hamayun; Jae-Ho Shin; Muhammad Kamran; Ahmed Al-Harrasi; Byung-Wook Yun; Muhammad Adnan; et al. (World Journal of Microbiology and Biotechnology, 2013)

The diversity of Rhizobia, Sinorhizobia and novel non-Rhizobial Paenibacillus nodulating wild herbaceous legumes - Sadia Latif; SamiUllah Khan; Muhammad Naveed; Ghulam Mustafa; Tasmia Bashir; Abdul Samad Mumtaz (Archives of Microbiology, 2013)

Synthesis and biological evaluation of new [1,3,4]thiadiazepino[7,6-b]quinolin-2-amines as potent anti-microbial agents - Hasnain Muhammad Raza; Nada-E-Ali Rizvi; Hamid Latif Siddiqui; Arshad Javaid; Mazhar Iqbal (Medicinal Chemistry Research, 2013)

LONG‐TERM EFFECTIVENESS OF LINING TERTIARY CANALS IN THE INDUS BASIN OF PAKISTAN - Ali Raza; Muhammad Latif; Abdul Sattar Shakir (Irrigation and Drainage, 2013)
This study was conducted to determine the effectiveness of lining tertiary canals with respect to their lining age. Twenty partially lined canals (1–25 years of lining age) were randomly selected and these were classified into five age groups with a class interval of 5 years. The flow rate of each selected channel was measured at the head and tail of the lined sections, and in the unlined sections at a distance equal to the length of the lined sections. The conveyance losses varied from 0.76 to 1.31 l s ‐1 per 100 m length. The lowest losses were observed in the newly lined canals (1– 5 years old) while the highest losses were observed in the case of group IV, having a lining age of between 16 and 20 years. The conveyance losses were reduced by 47 and 30% respectively in groups I and V. Thus, these results clearly demonstrate that the effectiveness of lining decreases with its age. A significant amount of water is saved by the newly lined canals; however, this benefit decreases as the lining become older. Copyright © 2013 John Wiley & Sons, Ltd.

Problems encountered in bicistronic IRES-GFP expression vectors employed in functional analyses of GC-induced genes - Muhammad Mansha; Muhammad Wasim; Christian Ploner; Abrar Hussain; Asma Abdul Latif; Muhammad Tariq; Anita Kofler (Molecular Biology Reports, 2012)

Novel quinolyl-thienyl chalcones and their 2-pyrazoline derivatives with diverse substitution pattern as antileishmanial agents against Leishmania major - Syed Umar Farooq Rizvi; Hamid Latif Siddiqui; Muhammad Nisar Ahmad; Matloob Ahmad; Mujahid Hussain Bukhari (Medicinal Chemistry Research, 2012)

Exophiala sp.LHL08 association gives heat stress tolerance by avoiding oxidative damage to cucumber plants - Abdul Latif Khan; Muhammad Hamayun; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Duk-Hwan Kim; In-Jung Lee (Biology and Fertility of Soils, 2012)

Pure culture of Metarhizium anisopliae LHL07 reprograms soybean to higher growth and mitigates salt stress - Abdul Latif Khan; Muhammad Hamayun; Sumera Afzal Khan; Sang-Mo Kang; Zabta Khan Shinwari; Muhammad Kamran; Shafiq ur Rehman; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2012)

Mutualistic association of Paecilomyces formosus LHL10 offers thermotolerance to Cucumis sativus - Abdul Latif Khan; Muhammad Hamayun; Ramalingam Radhakrishnan; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Jae-Ho Shin; Yeon-Sik Choo; Jong-Guk Kim; In-Jung Lee (Antonie van Leeuwenhoek, 2012)

Influence of Short-Term Silicon Application on Endogenous Physiohormonal Levels of Oryza sativa L. Under Wounding Stress - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Hamayun; Sang Mo Kang; Yoon Jung Beom; In-Jung Lee (Biological Trace Element Research, 2011)

Heterologous expression of a gene for thermostable xylanase from Chaetomium thermophilum in Pichia pastoris GS115 - Abdul Ghaffar; Sher Afzal Khan; Zahid Mukhtar; Muhammad Ibrahim Rajoka; Farooq Latif (Molecular Biology Reports, 2011)

Flexibility analysis of irrigation outlet structures using simulation of irrigation canal hydrodynamic model - Javaid A. Tariq; Muhammad Latif (Irrigation Science, 2011)

Assessment of water quality of a river using an indexing approach during the low‐flow season - Muhammad Tousif Bhatti; Muhammad Latif (Irrigation and Drainage, 2011)
The River Chenab is one of the largest rivers in Pakistan with an average annual flow of 5.29 billion cubic metres (BCM). The river traverses a total length of 576 km through a number of densely populated and industrial cities in the Punjab province of Pakistan. In the present study, a segment of 292 km was monitored for a variety of cardinal water quality constituents during the low‐flow months of 2006–07 and 2007–08. Water quality indices (WQIs) were calculated for three uses of the river water, i.e. irrigation, drinking and aquatic life, using the CWQI 1.0 model developed by the task group of the Canadian Council of Ministers of the Environment (CCME). The results revealed that the lower river reach (185–233 km) was more polluted than the upper 185 km segment. In this river reach, overall WQI ranking was poor for drinking and marginal for both irrigation and aquatic life. The WQIs for all three uses were ranked poor at the sampling station located at 233 km along the river. Copyright © 2009 John Wiley & Sons, Ltd.

Improving Operational Performance of Farmers Managed Distributary Canal using SIC Hydraulic Model - Javaid A. Tariq; Muhammad Latif (Water Resources Management, 2010)

Seasonal variations in the isotopic composition of leaf and stem water from an arid region of Southeast Asia - Saira Butt; Mubarik Ali; Muhammad Fazil; Zahid Latif (Hydrological Sciences Journal, 2010)

Growth promotion of cucumber by pure cultures of gibberellin-producing Phoma sp. GAH7 - Muhammad Hamayun; Sumera Afzal Khan; Abdul Latif Khan; Dong-Sheng Tang; Javid Hussain; Bashir Ahmad; Yasir Anwar; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2010)

Gibberellin production by pure cultures of a new strain of Aspergillus fumigatus - Muhammad Hamayun; Sumera Afzal Khan; Mir Ajab Khan; Abdul Latif Khan; Sang-Mo Kang; Sang-Kuk Kim; Gil-Jae Joo; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Groundwater and soil salinity variations in a canal command area in Pakistan - Muhammad Latif; Muhammad Zakria Ahmad (Irrigation and Drainage, 2009)
This three‐year study was undertaken to investigate the groundwater and soil salinity variation in a canal‐irrigated area. Water and soil samples were collected along 54 tertiary canals located on six secondary canals (two each at head, middle and tail end) of a main canal. Data of crop yield and income of the farmers were also collected. The results show that electrical conductivity (EC) of groundwater increased from head to lower reaches along all the irrigation channels, i.e. main, the secondary and the tertiary canals. Similarly, the soil water EC e also increased with increased distance from the head of the irrigation system. Reduced canal water supply at lower reaches of the irrigation system forced the downstream water users to pump more groundwater, thereby increasing their irrigation cost. The deteriorating groundwater quality further adds misery to the downstream farmers by degrading productivity of their lands caused by excessive use of saline groundwater. Location of the water users along the canal irrigation system had an impact on their crop yield as well as income and these parameters decreased with increased distance from the head of the irrigation channels. For example, the net income of the tail‐end farmers varied from 43% to 59% of the head‐end farmers. Copyright © 2008 John Wiley & Sons, Ltd.

Performance assessment of irrigation management transfer from government‐managed to farmer‐managed irrigation system: a case study - Muhammad Latif; Javaid A. Tariq (Irrigation and Drainage, 2009)
The government of NWFP, Pakistan, established an autonomous body, the Frontier Irrigation and Drainage Authority (FIDA), in 1997 to effectively cope with the emerging challenges in irrigation management. Six distributaries were recently transferred to farmers' organizations under the irrigation management transfer (IMT) for their operation and management. Results of the study revealed that the irrigation supplies are adequate to meet the crop water requirements. The relative water supply (RWS) index varies from 1.66 to 2.02 during summer, whereas in winter it varies from 2.22 to 2.55. The delivery performance ratio (DPR) during summer varies from 0.78 to 0.83 and in winter from 0.73 to 0.63. Irrigation supplies were reliable during both summer and winter seasons. Due to improved irrigation supply, annual irrigation intensity has increased by 25%. There is a prominent increase in yield of maize (40%), sugarcane (55%) and wheat (43%). The irrigation service fee collected was approximately 60% of the fee assessed. Hydraulic committees at each distributary should be established to operate the distributary according to crop demand. Awareness of the farmers should be created regarding the farm irrigation application methods to avoid over‐irrigation and wastage of water. Copyright © 2008 John Wiley & Sons, Ltd.

Purification and characterization of xylanases from Thermomyces lanuginosus and its mutant derivative possessing novel kinetic and thermodynamic properties - Syed Ali Imran Bokhari; Farooq Latif; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2009)

Fabrication and evaluation of a portable long‐throated flume - Ali Raza; Muhammad Latif; Ghulam Nabi (Irrigation and Drainage, 2007)
This study was conducted to test the performance of a locally fabricated portable long‐throated flume. Flow was measured over a range of 5–70 l s −1 and sharp crested v‐notch weir was used as a reference device. The measured flow was compared with a theoretical rating table generated by WinFlume software for a flume of same specification. The results indicate a difference of −0.20 to +2.04% between the measured and theoretical flow rates. The theoretical rating tables are generated with an error limit of ±2%, therefore the results are acceptable. The results of this study confirmed that portable long‐throated flumes are reliable and can be easily designed, by using the publicly available WinFlume software, and could be fabricated to suit local requirements. Copyright © 2007 John Wiley & Sons, Ltd.

Spatial productivity along a canal irrigation system in Pakistan - Muhammad Latif (Irrigation and Drainage, 2007)
This study was undertaken to investigate the impact of location on productivity of the farmers along an irrigation network in Pakistan. Data were collected from 54 tertiary canals situated along six secondary canals: two each at the head, middle and tail end of the main canal. Results revealed that location of the farms has a significant impact on farmers' productivity on different reaches along all the irrigation channels, i.e. the main canal, the secondary and the tertiary canals. The productivity of the tail‐reach farmers varies from one‐third to one‐half of their head‐ reach counterparts. The overall finding of this study is that location of the water users along the canal irrigation system has a significant impact on their income as well as productivity, and these parameters decrease with increase in distance from the head of the irrigation canals. The reduced canal water supply at the lower reaches of the irrigation system forced these water users to pump more groundwater, resulting in a many times increase in their irrigation costs. Additionally, groundwater quality deteriorates all along the irrigation channels (i.e. along the main canal, the secondary and tertiary canals), compounding the misery of the downstream farmers by degrading productivity of their lands because of increased soil salinity. Copyright © 2007 John Wiley & Sons, Ltd.

Purification and Characterization of a Xylanase Produced by Chaetomium thermophile NIBGE - Farooq Latif; Muhammad Asgher; Rabia Saleem; Ahmed Akrem; R. L. Legge (World Journal of Microbiology and Biotechnology, 2006)

A simple procedure for simulating surge infiltration using first‐surge infiltrometer data - Sajid Mahmood; Muhammad Latif (Irrigation and Drainage, 2005)
The objective of this study was to modify a ring infiltrometer and to develop a simple and generic technique for simulating cumulative infiltration under constant on‐time surge cycles. A ring infiltrometer was modified by connecting a pipe arm for inward and outward water flow to the ring and from the ring to the pipe to create on–off surge cycles respectively. The Kostiakov infiltration equation was modified by introducing“surge factors” to simulate infiltration data for subsequent surges, using first surge infiltrometer data. The modified form of the Kostiakov equation is called the, “Azeemi–Kostiakov equation”. The unknown parameters of the Kostiakov equation were determined by applying the two‐point technique. Results of the study revealed that the infiltration data simulated by the Azeemi–Kostiakov equation matched closely with those collected from the surge‐ring infiltrometer. A significant reduction in the cumulative infiltration during different surges was also observed which varies from 61 to 84% for the first surge and from 30 to 61% for the subsequent surges. On an overall basis, the significant advantage of the Azeemi–Kostiakov equation is its application in simulating cumulative infiltration of subsequent surges by successfully using limited infiltrometer data. The validity of the Azeemi–Kostiakov equation outside the conditions of the experiments and for varying on–off surge cycles needs to be verified in order to extend its applicability. If this is done, the prior estimation of infiltration for a desired set of on–off surge cycles through this method would permit planning of surge irrigation studies for efficient water management. Copyright © 2005 John Wiley & Sons, Ltd.

Field measurement and simulation of advance rates for continuous and surge irrigated furrows in Pakistan - Muhammad Latif; Sajid Mahmood (Irrigation and Drainage, 2004)
Field tests were conducted with inflow rates of 1.7–2.4 l s −1 to compare the advance rates both in continuous and surge‐irrigated furrows. The furrows were 149 m long, with 0.2–1.5% slopes. Water applied and rate of water advance were measured during five irrigation events. During the first irrigation, a reduction in applied water volume of 23–60% was observed in surge‐irrigated furrows compared with continuous irrigation. It was further noted during the course of the experiments that the surging effect was more pronounced during the first irrigation than in the subsequent irrigation events. However, it was noted that there would be hardly any benefit of the surge for smaller field lengths of 61 m, which are commonly used in Pakistan and many other developing countries. Results simulated by the SIRMOD model revealed that the water front advance curves matched closely with the observed ones in most surge treatments. The simulated performance efficiencies encourage the use and adaptation of surge irrigation in Pakistan, but more field studies are needed for its verification and for making concrete recommendations for its use in farmers' fields. Copyright © 2004 John Wiley & Sons, Ltd.

Irrigation management turnover: an option for improved utilization of limited water resources in Pakistan - Muhammad Latif; Muhammad Saleem Pomee (Irrigation and Drainage, 2003)
Underperformance of the irrigation systems and poor cost recovery from irrigated area in Pakistan have been a source of concern for the last few decades and since then it has been the subject of considerable external assistance and internal policy reforms. To address these problems in the management of irrigation systems, the World Bank proposed a number of institutional changes for irrigation management turnover (IMT). After thorough consideration it was decided to decentralize instead of privatizing the irrigation system management and to promote farmers' participation in the system management. Under these reforms, management at secondary canal level has recently been handed over to the farmers' organizations (FOs) of selected distributaries at a pilot scale. This study was designed to evaluate the farmer‐managed distributary in southern Punjab. Initial field measurements revealed that hydraulic aspects of the irrigation service delivered by the FO management have been significantly improved and as a result a highly proportionate and equitable water distribution pattern was observed, particularly at the tail reaches of the distributary during the post‐transfer scenario. Due to effective FO management farmers' interventions to increase the outlet discharge by illegal means have almost ceased. As a result of these improvements made by the FO in system management the extent of irrigated area has on average increased by 6–7% even under severe drought and continued famine‐like conditions prevailing in the country during recent years. Most importantly, cost recoveries have increased by an amount of 14% for summer and 23% for winter growing seasons respectively from the irrigated area of the distributary. Thus experience from the Hakra 4‐R distributary has shown that even under undesirable natural circumstances IMT was quite effective in achieving the key targets of the institutional reforms launched at pilot scale in the country. Copyright © 2003 John Wiley & Sons, Ltd.

The role of controlled drainage under drought conditions in an irrigated area in NWFP, Pakistan - Gul Daraz Khan; Muhammad Latif; Sibtul Hassan (Irrigation and Drainage, 2003)
The River Swat is the source of irrigation for the entire irrigation system of Mardan, Nowshera and Charsadda districts. Reductions of water and overdrainage have influenced the yield of major crops. The impact of reduced supply at the inlet from the source, drought conditions and overdrainage from the area have lowered the groundwater to a disastrous level. Thus the present groundwater level cannot contribute to the crops. A subsurface collector at its exit in drainage unit 106 was controlled to raise the watertable. The study area was divided into 10 zones. Each zone was separately assessed to analyze the groundwater impact in response to the controlled technique adopted for mitigating drought in different strategies of the canal operation. The interaction of groundwater level with irrigation depth, crop yield, water use efficiency and water saving were also studied. During the rotational period of the canal, irrigations applied in section II raised the water level by nearly 1 m. The upslope area of section III also needed a large irrigation depth. The groundwater level on the downslopes of the lateral drains in sections I and V was at the design depth of 1.1 m during the rotational strategy, while it decreased only slightly on the upslopes of the lateral drains for the same positions. Because of effective control by the collector, the watertable on the downslopes of the laterals in sections II and III was affected less while in the respective upslope area of section III it dropped more than 2 m. The water levels in section IV (both in the upslope and downslope areas along the laterals) remained very close to the design level. A significant contribution of seepage in the upslope of the collector drain considerably reduced the irrigation depths. During the canal closure period, the watertables in the study area dropped to the limit from 2.3 to 3.25 m. After the reopening of the canal, the watertables in sections II, III and IV were raised from 2.55 to 0.70 m. During this period the water levels near the canal reached the design level. The maximum yield of 6.5 tons ha −1 on the downslopes of the lateral drains in section II was obtained, resulting in maximum water use efficiency of 0.93 kg m −3 . However, the minimum yield of 3.5 tons ha −1 on the upslopes of the lateral drains in section I was obtained, resulting in the lowest water use efficiency of 0.35 kg m −3 near the deep surface drain (5 m). The impact of controlled subsurface drainage in zones 2, 3 and 7 resulted in the best maintenance of optimum groundwater level and moisture content. Therefore large amounts of extra irrigation water applied (ranging from 23 to 129% of that actually required) in different zones of the controlled area can be saved for drought conditions. Copyright © 2003 John Wiley & Sons, Ltd.